Enhanced thermal stability and flame retardancy of polyurethane foam composites with polybenzoxazine modified ammonium polyphosphates. Issue 16 (2nd February 2016) - Luo, Fubin; Wu, Kun; Lu, Mangeng
Abstract : The influence of polybenzoxazine modified ammonium polyphosphate (BMAPP) on the thermal behavior and flame retardancy of a rigid polyurethane foam (PU) are investigated using various techniques. Abstract : The influence of polybenzoxazine modified ammonium polyphosphate (BMAPP) on the thermal behavior and flame retardancy of a rigid polyurethane foam (PU) are investigated via thermogravimetric analysis (TG), TG coupled with infrared spectroscopy (TG-FTIR), UL-94 vertical burning testing and limit oxygen index (LOI). The TG testing results indicate that BMAPP can enhance the thermal stability of PU, both under air and nitrogen conditions. The initial degradation temperature of the BMAPP/PU composites is 264 °C in air, which is 22 °C and 30 °C higher than that of ammonium polyphosphate (APP)/PU composites and neat PU, respectively. The reason might be attributed to the better dispersion and compatibility of BMAPP particles in PU compared with APP, which can prevent the PU chain from degrading at low temperatures. The LOI value results demonstrate that BMAPP has higher flame retardancy in PU than APP. Residue analysis implies that polybenzoxazine is partially converted into Si–O as char residue during combustion.